COVID-19 Biomarkers for Critically Ill Patients: A Compendium for the Physician - Federica Arturi; Gabriele Melegari; Antonio Giansante; Enrico Giuliani; Elisabetta Bertellini; Alberto Barbieri (MDPI AG, 2023)
Background: SARS-CoV-2 clinical manifestation and progression are variable and unpredictable, hence the importance of considering biomarkers in clinical practice that can be useful for both diagnosis and prognostic evaluation. This review aims to summarize, for intensive care physicians, the most recent state of knowledge regarding known COVID-19 in critical patients. We searched PubMed® using the Boolean operators and identified all results on the PubMed® database of all studies regarding COVID-19 biomarkers. We selected studies regarding endothelium, cytokines, bacterial infection, coagulation, and cardiovascular biomarkers. Methods: We divided the results into four essential paragraphs: "Cytokine storm", "Endothelium dysfunction and coagulation biomarkers in COVID-19", "Biomarker of sepsis", and Cardiovascular lung and new perspectives. Results: The assessments of the severe COVID-19 prognosis should monitor, over time, IL-6, soluble Von Willebrand factor (VWF), P-selectin, sCD40L, thrombomodulin, VCAM-1, endothelin- Troponin, D-dimer, LDH, CRP, and procalcitonin. Metabolomic alterations and ACE2 receptors represent new perspectives. Discussion and Conclusions: Early identification of critically ill patients has been crucial in the first COVID-19 pandemic wave for the sustainability of the healthcare emergency system and clinical management. Only through the early identification of the most severe patients can they be provided with the most appropriate treatments.